Antitumor activity of β-2-himachalen-6-ol in colon cancer is mediated through its inhibition of the PI3K and MAPK pathways. (25th September 2017) - Daaboul, Hamid E.; Daher, Costantine F.; Bodman-Smith, Kikki; Taleb, Robin I.; Shebaby, Wassim N.; Boulos, Joelle; Dagher, Carole; Mroueh, Mohamad A.; El-Sibai, Mirvat
Abstract: Previous studies in our laboratory showed that Daucus carota oil extract (DCOE) possesses in vitro and in vivo anticancer activities. Chemical analysis of DCOE led to the isolation of β -2-himachalen-6-ol (HC) which exhibited potent anticancer activity against colon, breast, brain and skin cancer cells. The present study investigates the anticancer activity of HC against SW1116 colon cancer cell lines, and evaluates its effect in a 1, 2-dimethylhydrazine (DMH) colon carcinogenesis black6 mice model. The SW1116 colon cancer cell line was treated with HC (1, 5, 10 and 25 μg/ml) and cell viability was evaluated with WST 1 assay kit. Cell cycle analysis was carried out by flow cytometry, and pro/anti-apoptotic proteins were measured using western blot. The effect of intraperitoneal (IP) treatment with HC (10, 25 and 50 μg/ml) in mice was assessed using the DMH colon carcinogenesis model with Cisplatin (2.5 μg/kg; IP) as a positive control. Blood samples were collected for assessment of liver toxicity and colon tumor incidence and size were studied histologically. HC showed a dose-dependent decrease in cell survival with an IC50 of 18 and 14.5 μg/ml after 24 and 48 h respectively. Flow cytometry analysis revealed that 10 μg/ml HC increased the number of cells undergoing necrosis (18.05%) and late apoptosis (15.66%). At HC 25 μg/ml more cells shifted toward necrosis (58.01%) and late apoptosis (30.47%). Western blot analysis revealed a significant decrease in p -Erk, p -Akt, pro-caspase-3 and Bcl-2 and an increase in p53, p21, Bax and PARP proteins. Mice treatment (IP) with HC caused a significant decrease in tumor incidence and size. Similar effects were observed with cisplatin treatment. In conclusion, HC treatment (low dose) induced cell cycle arrest and promoted apoptosis via inhibition of the MAPK/ERK and PI3K/AKT pathways. HC treatment also had antitumor effect in vivo with no significant toxicity to laboratory mice. Highlights: β -2-himachalen-6-ol (HC) exhibited potent anticancer activity against the grade 3 colon adenocarcinoma cells SW1116. HC showed less nephrotoxicity than cisplatin in vivo . HC led to apoptosis in colon cancer cells through the inhibition of the PI3K pathway and the ERK pathway. HC treatment also had antitumor effect in vivo with no significant toxicity to laboratory mice.